Appendiceal goblet cell carcinoid tumor with endometrial metastasis - Reyna-Villasmil, Eduardo (2022)
Goblet cell carcinoid tumor is an almost exclusive mixed neoplasm of the appendixwith neuroendocrine and mucinous differentiation. Endometrial metastaticinvolvement by extragenital carcinomas, especially the signet ring cell type, is rare.A case of appendiceal goblet cell carcinoid tumor with endometrial metastasisis presented. This was a 70-year-old female patient who presented with genitalbleeding. The gynecological examination showed moderate red-brown genitalbleeding and hardened cervix. Endometrial biopsy reported nests of signet ringcells. The provisional diagnostic impression was poorly differentiated carcinoma ofprobable intestinal origin. During surgery, the uterus had a stony consistency, thececal appendix was fibrotic and thickened, and the omentum was thickened withtumor nodules. Anatomical sections of the cervix and uterine body showed tumorfoci. In the cecal appendix, small clusters composed of goblet cells were found.Immunostaining was positive for synaptophysin, CDX-2, EMA, CK20, focal CD56.These findings confirmed the diagnosis of goblet cell carcinoid tumor, a tumorcharacterized by infiltration of the appendiceal wall by small nests or cords of gobletcells with intracytoplasmic mucin and focal expression of neuroendocrine markers.These neoplasms have a more aggressive behavior than neuroendocrine tumors.Endometrial metastasis is rare and can be mistaken for a primary signet ring cellcarcinoma. It should be considered as a differential diagnosis after other primarytumors have been excluded.